Expert System Application Detecting Child Personal Characteristics Using Forward Chaining Method - Meti Nurhayati; Sari Noorlimayanti (Journal of Information System, Informatics and Computing, 2022)
The growth and development of a child as the next generation of the nation is influenced by the family environment. Parents must be good nannies because they are the ones who shape their personality. Children in a family are born with different personalities but parents play a very important role in controlling children's behavior in life. Knowledge of parents about the characteristics and personality of children who are less likely to consult psychology. Good parents certainly try to direct children with the personality and characteristics of the child so that it does not become a problem in the future. Child delinquency is a form of character and personality that should be controlled for the better. These problems can be anticipated by seeking knowledge about the child's psychology. Based on this explanation, this research was carried out by developing an application of information on children's personality knowledge which can assist parents in monitoring children's development. This developed application contains an expert system where the results of the explanation are based on the knowledge of the experts. Development of expert system application development of child personality information using PHP and MySQL with forward chaining inference method. The developed application provides information on the symptoms the child has until it is known which group the characteristics belong to. How the forward chaining method works by processing interpretation, regulation, supervision and planning. Users enter answers based on questions collected from expert knowledge where the results of the calculation of user answers determine the personality group and characteristics of the child